Efeito do congelamento e de hidrocoloides sobre as características de sobremesa láctea tipo cheesecake - Silva, Ana Paula Alves da (2021)
Freezing is a widely used method to preserve the sensory and nutritional properties of foods. Moreover, it reduces chemical and physical reactions in order to maintain food quality and safety. However, this process can cause changes in food due to the formation of ice crystals, which damage the microstructure of the cellular matrix, changing the final product. The use of hydrocolloids is an option to minimize the effects of freezing due to their stabilizing properties. Desserts are widely consumed around the world, comprising part of the diet. Dairy dessert needs refrigeration as they are perishable. This study aimed to evaluate the effects of freezing and different hydrocolloids added to cheesecake desserts on physicochemical and sensory characteristics. Formulations were produced with the hydrocolloids (carboxymethylcellulose (CMC), guar gum and xanthan gum), as well as a standard formulation. Then, samples were frozen in a conventional freezer (-20ºC) and ultrafreezer (-70ºC) and characterized for texture,color, pH, water activity, syneresis and sensory analysis. The addition of hydrocolloids and freezing did not significantly change the pH and syneresis of the cheesecakes evaluated. Conventional freezing decreased water activity values. Freezing process caused increase in luminosity of cheesecakes with increase in yellowish color. The addition of CMC and xanthan gum increased hardness of cheesecakes. Freezing process also influenced hardness of cheesecakes with xantan gum. Adhesiveness of all cheesecakes was equal to the standard cheesecake, that is, the process did not affect this property. The acceptability showed that the addition of hydrocolloids and the freezing process had no negative influence on appearance, color, texture and overall impression, but showed influence on the flavor parameter, although all cheesecakes have been equal to the standard cheesecake. It was concluded that the freezing process at -70°C is indicated for cheesecake storage, as it caused less physical, chemical and sensory changes in the samples. Regarding the use of hydrocolloids in this dessert, their addition did not bring benefits under the conditions evaluated.